PENGARUH PROMOSI DAN DAYA BELI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN BARANG PADA TOKO RITEL PT INDOMARCO PRISMATAMA CABANG CIGONDEWAH KALER BANDUNG - RAMAYANI YUSUF RAMAYANI YUSUF (EKBIS (Ekonomi & Bisnis), 2018)
The purpose of research is to know the influence of promotion and Purchase Power to Purchase Decision at retail store PT Indomarco Prismatama Branch Cigondewah Kaler Bandung.The method that is used in conducting this research is the method quantitative descriptive, with data collection based on observation, questionnaires and interviews. The data collected is then analyzed by using statistical test of correlation and determination coefficient.The data of this research is obtained from consumer data PT Indomarco Prismatama branch Cigondewah Kaler Bandung. From the results obtained correlation coefficient of 0,890. This tells that there is a very close relationship between Promotion of Purchase Decision, as it is at the interval of 0,80 to 1,00 then the Promotion variable (X1) has an effect on the Consumer Purchases Decision and Purchase Power (X2) have less influence on Buying decision.In this research is found problems that happened, the lack public purchasing power to purchase goods at retail stores PT Indomarco Prismatama so that causing a decrease in store revenue and its efforts ar Indomaret must be more active employees in carrying out promotions directly to consumers or customers and reproduce promo products so consumers can shop more.